UnaG as a reporter in adeno‐associated virus‐mediated gene transfer for biomedical imaging. Issue 12 (15th September 2020) - Liu, Yurong; Zhang, Huimin; Chen, Ruixi; Wu, Ying; Yang, Xiong; Liu, Xiuli; Zeng, Shaoqun; Guo, Wenyan
Abstract: Adeno‐associated virus (AAV) is one of the most common gene transfer vectors, but it has a limited capacity. A smaller fluorescent protein is urgently needed since it is more suitable to act as a reporter in AAV. In this study, a bilirubin‐dependent reporter smaller than EGFP, termed UnaG, was found to have the ability to label the neurons of a mouse brain as clearly as EGFP without the addition of exogenous bilirubin. We also found that UnaG's pH tolerance is better than that of EGFP; however, its fluorescence recovery after protonated quenching is not as good as that of EGFP. In addition, UnaG preserved its fluorescence better than EGFP in SeeDB clearing. Taken together, this study demonstrates that UnaG can act as a small intrinsically fluorescent reporter in the mouse brain without an additional ligand, thus providing an alternative over EGFP for AAV‐mediated neuron labeling in mammals. Abstract : UnaG, a bilirubin‐inducible extrinsically fluorescent tag from vertebrates, can act as a small intrinsically fluorescent reporter in the mouse brain without an additional ligand. It can label the neurons morphology as well as EGFP. It shows better performance in SeeDB tissue clearing than EGFP. In sum, UnaG provides an alternative over EGFP for AAV mediated neurons labeling in mammals for biomedical imaging.